State Capture and Security Intelligence Agencies in Serbia - Petrovic, Predrag (Journal of Regional Security, 2021)
Security intelligence agencies play a central role in state capture. Due to the very nature of how they are organised and operate, security intelligence agencies first become targets of these processes, before becoming their principal agents. Indeed, political elites and security intelligence agencies become natural partners in this endeavour, with the very process of state capture coming to resemble a complex intelligence operation. Even though the experiences of many countries bear this out, attempts to research the role of security intelligence agencies in a systematic and theoretically grounded manner remain rare. By using recent theoretical approaches defining state capture as a deliberate political undertaking, the main goal of which is the acquisition of unrestricted state power that in turn enables the unhindered and unsanctioned pursuit of the narrow interests of political elites to the detriment of the public good, this study aims to determine the factors, conditions and mechanisms that facilitate the rapid capture of security services and their further use in capturing the state. This will be explored through the example of Serbia – a country that, two decades on from the start of its democratic transformation, is now a captured state sliding towards autocracy.